Inequality and tax regressivity during the Brazilian independence (1808-1836) - Eduardo Silva-Ramos (América Latina en la Historia Económica)
This paper aims to discuss some aspects of the taxation system genesis and to present a brief highlight about the Bank of Brazil and the National Treasury’s role in the Brazilian economic policy during the nineteenth century. We also discuss the main state and social aspects of Brazilian taxation: regressivity and fiscal privileges to the richer classes. Our goal is to indicate the conflictive nature of these institutions, as well as the distinct options that materialized in the Brazilian State formation first moments. We emphasize that the Brazilian economic formation was not unalterable and inevitable.